Scientific production of the Portuguese and Spanish universities: a comparative analysis - Costa, Teresa; Rodríguez-Bravo, Blanca (Qualitative and Quantitative Methods in Libraries, 2017)
Increasingly higher education institutions play a key role in research and scientific production. In every country and region the production’s thematic orientation of universities presents particular characteristics. The need of identify outstanding institutions had as consequence a variety of papers that compare the main thematic orientation of universities in an international level (Bordons et al., 2010; Souza et al. 2015).  This study analyses the scientific production of universities in Portugal and Spain in the period between 2005 and 2014. We used the Web of   Science (WoS) from which we identified their subject area specialization.   The objective is to know and compare the contribution of universities in each of these countries and identify their thematic specialization profiles through the usage of bibliometric and statistical indicators. The analysis will present tendencies of the scientific production comparing and relating the situation of Portugal and Spain. The results show that 66% of the Spanish scientific output corresponds to the production of higher education institutions, while the Portuguese values of this type of institutions reach 84% of the total.  We identified the main research areas and conclude that the subject areas with more production indexed in WoS are Engineering, Chemistry, Physics and Computer Science in both countries. Besides we identified the collaboration in research output between both countries and with other countries. These results give valuable information to recommend strategies for the cooperation between universities of both Iberian countries in order to increase their visibility and impact worldwide.